PENGARUH KOMISARIS INDEPENDEN,KEPEMILIKAN INSTITUSIONAL, KOMITE AUDIT, UKURAN KAP, DAN LEVERAGE TERHADAP INTEGRITAS LAPORAN KEUANGAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2016) - Susiwo, 14.05.52.0203; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2018)
This study examines the influence of Independent Commissioners, Institutional Ownership, Audit Committee, KAP Size, and Leverage on the Integrity of Financial Statements in Manufacturing Companies Listed on the Indonesia Stock Exchange. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2014-2016. This research uses purposive sampling method. The equipment in this study uses multiple linier regression, partial test (t test) and simultaneous test (f test). This study found that leverage variables have a significant negative effect on the integrity of financial statements. Whereas Independent Commissioners, institutional ownership, audit committee, KAP size have a significant positive effect on the integrity of financial statements. Keywords: Integrity of Financial Statements, Independent Commissioners, Institutional Ownership, Audit Committee, KAP Size, and Leverage